Do tamanho do mundo : regionalidade e universalidade na obra Sagarana, de J. Guimarães Rosa - Pelinser, André Tessaro (My University, 2014)
This paper discusses the presence of the regionality and the universality in the work Sagarana, by João Guimarães Rosa. Therefore, it uses theoretical principles from the studies on social imaginary and cultural identity, intending to analyze the contribution of imaginary and identity elements for constructing the regionality of the fictional universe represented, as well as for expressing its intended universality. It examines several forms of symbolic representations valued in the region and the way they enclose aspects of universality, translated into literary language. It´s an interdisciplinary discussion concerning Literature, Sociology and Anthropology, which is connected to the regionality studies.
Este trabalho discute a presença da regionalidade e da universalidade na obra Sagarana, de João Guimarães Rosa. Para tanto, são utilizados fundamentos teóricos oriundos dos estudos sobre imaginário social e identidade cultural, visando analisar a contribuição dos elementos imaginários e identitátios para a construção da regionalidade do universo ficcional representado, bem como para a expressão de sua pretendida universalidade. Examinam-se diversas formas de representações simbólicas valorizadas na região e como elas encerram aspectos de universalidade, vertidos em linguagem literária. Trata-se de uma discussão interdisciplinar apoiada na Literatura, na Sociologia e na Antropologia, inserida no contexto dos estudos da regionalidade.
Keywords: LETRAS; João Guimarães Rosa; Sagarana; Regionalidade; Universalidade; Imaginário social; Identidade cultural; João Guimarães Rosa; Sagarana; Regionality; Universality; Social imaginary; Cultural identity